2008
DOI: 10.1104/pp.108.120014
|View full text |Cite
|
Sign up to set email alerts
|

pur4 Mutations Are Lethal to the Male, But Not the Female, Gametophyte and Affect Sporophyte Development in Arabidopsis

Abstract: Purine metabolism is crucial in living cells and involves three complex pathways in plants: the de novo synthesis, the salvage, and the degradation pathways. The relative importance of each pathway in plant development and reproduction, however, is still unclear. We identified two T-DNA insertions in the Arabidopsis (Arabidopsis thaliana) PUR4 gene (At1g74260) that encodes formylglycinamidine ribonucleotide synthase (EC 6.3.5.3), the fourth enzyme in the de novo purine biosynthesis pathway. The mutated alleles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…These results illustrate how a coherent and easy-to-navigate data visualization scheme, such as the AraGenNet, can predict biologically meaningful relationships. Recently, the pollen-deficient mutant corresponding to the gene At1g74260 was confirmed by another study (Berthomé et al, 2008).…”
Section: Prediction and Verification Of Essential Genes In The Networkmentioning
confidence: 66%
“…These results illustrate how a coherent and easy-to-navigate data visualization scheme, such as the AraGenNet, can predict biologically meaningful relationships. Recently, the pollen-deficient mutant corresponding to the gene At1g74260 was confirmed by another study (Berthomé et al, 2008).…”
Section: Prediction and Verification Of Essential Genes In The Networkmentioning
confidence: 66%
“…Similar to dpd2, a T-DNA insertion mutant of formylglycinamidine ribonucleotide synthase (PUR4), which is defective in purine synthesis, also exhibits defective pollen development, such as pollen abortion, abnormal cytoplasm staining and impaired pollen mitosis (Berthomé et al, 2008). However, the presence of the dpd phenotype was not described in phenotypic analyses of pur4 by Berthomé et al (2008). Taken together, we suggest that maintenance of a balanced nucleotide pool by RNR is vital for pollen to develop normally.…”
Section: Possible Link Between Odd and De Novo Nucleotide Synthesismentioning
confidence: 90%
“…, 2008). However, the presence of the dpd phenotype was not described in phenotypic analyses of pur4 by Berthomé et al. (2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2008). Recently, it has been shown that a formylglycinamidine ribonucleotide synthase mutant ( pur4 ), defective in de novo purine biosynthesis, compromised male gametophyte development and to a smaller extent female gametophyte development (Berthome et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%